2018
DOI: 10.32832/manager.v1i1.1439
|View full text |Cite
|
Sign up to set email alerts
|

Brand Awareness In Retail Terhadap Consumer Purchase Intention

Abstract: <p>Brand Awareness In Retail Terhadap Consumer Purchase Intention (Studi<br />Kasus Pada Produk Belsoap Produksi PT Galenium Pharmasia Laboratories Tbk<br />di 20 Carrefour Se-Jakarta, Bogor, Depok. Univeritas Ibn Khaldun<br />Bogor).Kesadaran Merek (Brand Awareness) adalah salah satu hal yang dapat<br />menimbulkan minat beli konsumen pada sebuah produk. Adapun tahapan dari<br />kesadaran merek adalah unware of brand (belum mengingat brand), brand<br />recognition (pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…This shows that retailer brand has a significant and positive influence on Customer Purchase Intentions. The results of this research are in line with and strengthen research conducted by Kuraesin & Eldine (2018) which concluded that brand awareness in retail influences consumer purchase intention for Belsoap products. The importance of the retailer brand in shaping consumer purchasing intentions shows that the brand identity of the retailer has a significant and positive impact on purchasing decisions.…”
supporting
confidence: 88%
“…This shows that retailer brand has a significant and positive influence on Customer Purchase Intentions. The results of this research are in line with and strengthen research conducted by Kuraesin & Eldine (2018) which concluded that brand awareness in retail influences consumer purchase intention for Belsoap products. The importance of the retailer brand in shaping consumer purchasing intentions shows that the brand identity of the retailer has a significant and positive impact on purchasing decisions.…”
supporting
confidence: 88%